The Effects of a Charge Nurse Preparatory Program on the Perception of Managerial Roles of the Team Leaders in the Intensive Care Unit of a Tertiary Hospital - Srisai, Pinruetai; Chatdokmaiprai, Kannikar; Singchangchai, Phechnoy (NU Journal of Nursing and Health Sciences, 2025)
This research study is a quasi-experimental study with two groups taking the pre-test and the post-test. The purpose is to compare the managerial role perceptions of the nurses joining the program. The samples were selcted with the purposive sampling method. The size of the samples was 60 (including the experimental group with 30 samples abd the control group with 30 samples). There were two parts of the research instruments. The 1st part was the preparation program for Charge Nurse in the Intensive Care Unit. Personnel development and training concepts were used by the researcher(s) and consisted of the following processes: ) needs assessment, 2) design , 3) implementation, and 4) evaluations. The Charge Nurse were followed up by integrating the perception concepts of the eight role: 1) mentor role, 2) facilitator role, 3) innovator role, 4) Broker Role, 5) director role, 6) Producer Role, 7) coordinator role, and 8) Monitor Role. The 2nd part included the data collection tools: the general information questionnaires and the managerial role perception questionnaires. The qualities of the tools were checked by analyzing the content validity of 0.86 and Cronbach’s alpha of 0.93. The data were analyzed with the descriptive statistics (frequency, percentage, mean and standard deviation_ and the inferential statistics (independent t-test and dependent t-test). The findings showed that the managerial role perception scores of the nurses in the experimental group were high (X- = 4.88 SD = 0.11), while the scores of the control group were moderate (X-= 3.15 SD = 0.14). By comparing the average scores, it was found that the managerial role perception scores of the experimental group’s nurses as the Charge Nurse were significantly and statistically higher than the scores of the control group p < .05). The findings indicated that the managerial role perceptions of the team leader in the experimental group after joining the program were significantly and statistically higher than the perceptions before joing the program (p < .05). By studying the implementation of the preparation program for the for the team leader in the Charge Nurse, there were the good effects towards the preparations of the Charge Nurse. As a a result, the Charge Nurse the confidences in becoming first line nurse manager . The nursing managers should apply these findings to developing strategies for improving the performances of the Charge Nurse according to the performance standards of the Charge Nurse in other nursing organizations.